View of the Chaturmukha linga - Temples of India Project Team (Jio Institute, 2024)
The north face of the Chaturmukha linga has a jatamukuta (matted crown) but it is different from the other faces. Snail-shaped curls are carved above the forehead with hairlocks coming down to the shoulders. The deity is adorned with a beautiful necklace.